Modeling port competition from a transport chain perspective. (March 2016) - Song, Dong-Ping; Lyons, Andrew; Li, Dong; Sharifi, Hossein
Highlights: Model competitive ports with hinterland shipments and transhipments. Take a transport chain perspective including deep sea, feeder and inland transport. Present a non-cooperative game model for a two-ports-one-carrier system. Compare the decentralized non-cooperative model with centralized model. Illustrate the results in a case study of Southampton and Liverpool ports. Abstract: This paper considers the competition between two ports involving both hinterland shipments and transhipments. Taking a transport chain perspective including deep-sea, port, feeder and inland transportation, we present a static cost model to examine ports' relative competitiveness and justify the development of game models. A non-cooperative game model is then formulated for a two-ports-one-ocean carrier system. The optimal ports' pricing and the carrier's port-of-call decisions are derived. A centralized supply chain model is then discussed. The game model is further extended to uncertain demand situations. A case study of Southampton and Liverpool ports is provided to illustrate the results.